Ciri Geokimia Batuan Vulkaniklastika di daerah Tanjung Balit, Sumatra Barat: Suatu Indikasi Kegiatan Magma pada Eosen - Harahap, Bhakti H. (Geological Agency, 2010)
DOI: 10.17014/ijog.v5i2.94Volcaniclastic rocks exposed in the Tanjung Balit area, West Sumatra, are red in color, loose, soft, and fractured. The rocks are strongly altered to be clay with calcium (CaO) and natrium (Na2O) contents extremely low (0.02 and maximum 0.30wt% respectively), and high loss of ignition (LOI) (4-15wt%). Mobile minor elements such as strontium (Sr), rubidium (Rb), and lanthanum (La) are also changed as their values do not fit to a normal contents range of fresh volcanic rocks in general. Geochemical analyses of the rocks resulted in the following oxide values: silica (SiO2) ranges from 58 – 68wt%, alumina (Al2O3) 15,90 – 21,46wt%, magnesium (MgO) 1, 36 – 1.61wt%, iron oxides (Fe2O3) 4,8-6,9wt%, potassium (K2O) 2,73 - 4,23wt% and titanium (TiO2) 0,60 - 0,70wt%. In general, the element contents especially the immobile ones (Ti, Mg and Fe) show that the rocks were originated from magmatic activity, which is also supported by petrographical characteristics that are still showing felspar and quartz minerals relicts. Based on SiO2 versus K2O diagram, these rocks are classified as high K-calc-alkaline series and belong to an intermediate composition. The rocks of the above criteria such as high alumina, very low magnesium and less than 1% titanium are one of the evidences that they are a magmatic arc product. The trace element of the rocks is summarized on the spider diagram; here their patterns strongly resemble to the typical of magmatic arc as well with enrichment in large ion lithophile elements (LILE) and light rare earth elements (LREE) relative to high field strength elements (HFSE) and heavy REE (HREE). Trace element pattern and REE suggest they were originated from a high K- calc-alkaline magma source.